2019
DOI: 10.2174/1381612825666190206195808
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Product Development Exploiting 3D Printing Technology: Conventional to Novel Drug Delivery System

Abstract: Background: 3D printed pharmaceutical products are revolutionizing the pharmaceutical industry as a prospective mean to achieve a personalized method of treatments acquired to the specially designed need of each patient. It will depend upon age, weight, concomitants, pharmacogenetics and pharmacokinetic profile of the patient and thus transforming the current pharmaceutical market as a potential alternative to conventional medicine. 3D printing technology is getting more consideration in new medicine formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…3D printing of cells (bioprinting) also holds promise for patient-specific tissue fabrication as a regeneration therapy. 7,8) The contribution of 3D printing technology to personalized medical therapy is thus clearly expanding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3D printing of cells (bioprinting) also holds promise for patient-specific tissue fabrication as a regeneration therapy. 7,8) The contribution of 3D printing technology to personalized medical therapy is thus clearly expanding.…”
Section: Introductionmentioning
confidence: 99%
“…New pharmaceutical applications of 3D printing technology are increasing following the U.S. Food and Drug Administration approval of the manufacturing of a 3D printed tablet (SPRITAM) in August 2015. 9,10) This orodispersible tablet is manufactured in bulk using a powder-based 3D printer and ZipDose technology. Other types of 3D printers using various printer materials have been studied to explore novel applications of 3D printed pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, FDM technology can be used to produce materials with macro-scale to the nanoscale internal geometrical characteristics [43]. The first 3D-printed tablet (Spritam®) has met the FDA requirements, claiming the commercial vitality of FMD technique [41]. Another field where LAY-FOMM can find application is the manufacture of 3D-printed masks with pore size ranging from 16.90 to 146.60 μm [44] as additive manufacturing gives the opportunity to manipulate the pore size by changing the printer settings [45].…”
Section: Discussionmentioning
confidence: 99%
“…Research in the field of 3D printing in recent years has shown how diverse the areas of application of this manufacturing technology are, particularly in the pharmaceutical field. Since the approval of the first oral 3D-printed dosage form Spritam in 2015, many other studies have been conducted regarding the applicability of 3D printing for the production of a wide variety of dosage forms [1][2][3]. Among all the additive manufacturing techniques that belong to the field of 3D printing, fused deposition modeling (FDM) is the most widely used method for oral dosage forms [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%